2014
DOI: 10.1017/s1368980014000895
|View full text |Cite
|
Sign up to set email alerts
|

Consensus development on the essential competencies for Iranian public health nutritionists

Abstract: Objective: To assess key experts' opinion regarding essential competencies required for effective public health nutrition practice within the health-care system of Iran. Design: Qualitative study using the modified Delphi technique through an emaildelivered questionnaire. Setting: Iran. Subjects: Fifty-five experts were contacted through email. The inclusion criterion for the study panel was being in a relevant senior-level position in nutrition science or public health nutrition in Iran. Results: In the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
1
8
0
1
Order By: Relevance
“…Todas estas competências estão no arcabouço da Psicologia e vão ao encontro de necessidades destacadas pelos participantes da presente investigação. O mesmo estudo compara estes resultados com dados de outros países como Austrália, Canadá, Estados Unidos e dados europeus, mostrando resultados semelhantes quanto a tais competências 29 .…”
Section: Discussionunclassified
“…Todas estas competências estão no arcabouço da Psicologia e vão ao encontro de necessidades destacadas pelos participantes da presente investigação. O mesmo estudo compara estes resultados com dados de outros países como Austrália, Canadá, Estados Unidos e dados europeus, mostrando resultados semelhantes quanto a tais competências 29 .…”
Section: Discussionunclassified
“…A study carried out by Sadeghi-Ghotbabadi et al [46] compared the essential competencies for "PHN practice". The authors found that the ability to "asses and analyze" was the only common competency needed among some countries, such as Iran, Australia, Canada, the United States, and some European countries [46].…”
Section: Checklist For Qualitative Researchmentioning
confidence: 99%
“…Therefore, in terms of Public Health, in order to meet the demands of contemporary health care practice, the educational training of nutritionists must consider the practice aspects and the challenges of professional performance, taking into account the transformations in the labor market, the social determinants of health, the epidemiological and nutritional transition, the complexity of Chronic Non-Communicable Diseases (CNCD), and Food and Nutrition Security (FNS) dimensions [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations